2023
DOI: 10.1038/s41422-023-00789-0
|View full text |Cite
|
Sign up to set email alerts
|

Tuning charge density of chimeric antigen receptor optimizes tonic signaling and CAR-T cell fitness

Abstract: Tonic signaling of chimeric antigen receptor (CAR), i.e., the spontaneous CAR activation in the absence of tumor antigen stimulation, is considered to be a pivotal event controlling CAR-T efficacy. However, the molecular mechanism underlying the spontaneous CAR signals remains elusive. Here, we unveil that positively charged patches (PCPs) on the surface of the CAR antigen-binding domain mediate CAR clustering and result in CAR tonic signaling. For CARs with high tonic signaling (e.g., GD2.CAR and CSPG4.CAR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 59 publications
0
37
0
Order By: Relevance
“…We identified a few IDRs, including those from FUS, EWS, and TAF15, that promote the membrane-proximal signaling, cytotoxic factor production, and killing of CAR-Ts against low antigen-expressing cancers (CD19, CD22, and HER2). Moreover, no elevated tonic signaling was observed in IDR CAR-Ts, suggesting a difference in signaling outcomes between IDRinduced condensation and previously reported CAR aggregation (Chen et al, 2023;Long et al, 2015). Together, these results demonstrated that IDRs, though not originally linked to T cell signaling, can serve as a new modular motif to improve the anti-tumor effect of CAR-Ts.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…We identified a few IDRs, including those from FUS, EWS, and TAF15, that promote the membrane-proximal signaling, cytotoxic factor production, and killing of CAR-Ts against low antigen-expressing cancers (CD19, CD22, and HER2). Moreover, no elevated tonic signaling was observed in IDR CAR-Ts, suggesting a difference in signaling outcomes between IDRinduced condensation and previously reported CAR aggregation (Chen et al, 2023;Long et al, 2015). Together, these results demonstrated that IDRs, though not originally linked to T cell signaling, can serve as a new modular motif to improve the anti-tumor effect of CAR-Ts.…”
Section: Introductionmentioning
confidence: 53%
“…Previous work showed that aggregation of CARs targeting GD2 or CSPG4 induces tonic signaling, which triggers CAR-T activation in the absence of antigens (Chen et al, 2023; Long et al, 2015). Therefore, we assessed if IDR-induced CAR condensation causes tonic signaling.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that CAR molecules with more positively charged amino acid residues, or positively charged patches (PCP), in scFv are more likely to aggregate spontaneously and generate stronger electrostatic field and substrate signals. When the ionic strength in the environment is enhanced by increasing the concentration of sodium chloride in the enhanced CAR‐T medium, the aggregation of CAR molecules is effectively prevented and the tonic signal is significantly reduced 49 . After mutating several positively charged residues in the scFv framework region (FR) of a CAR molecule with large PCP to uncharged residues, the CAR‐T cells showed a significant reduction of tonic signaling.…”
Section: Car Tonic Signaling Is Determined By the Surface Charge Of T...mentioning
confidence: 99%
“…CAR‐T cells overexpressing the reduced positively charged CAR molecules were less exhausted and showed enhanced antitumor efficacy in vivo. Importantly, a metric to quantify positively charged patches on the CAR surface, the PCP score, was defined and can be used as a reliable predictor of tonic signaling of CAR molecules 49 . This study brings new design ideas to the CAR‐T field, in which the PCP score on the surface needs to be considered while constructing more powerful CARs.…”
Section: Car Tonic Signaling Is Determined By the Surface Charge Of T...mentioning
confidence: 99%
See 1 more Smart Citation